ANALISIS KEUNTUNGAN USAHA INDUSTRI RUMAH TANGGA KOPI ROBUSTA BUBUK BIJI MERAH DI DESA LIBERIA TIMUR KECAMATAN MODAYAG KABUPATEN BOLAANG MONGONDOW TIMUR (Business Profit Analysis Of Household Industry Of Robusta Coffee Red Seed Powder In East Liberia Village, Modayag Sub District, East Bolaang Mongondow Regency) - Vieky Mirah; Audrey J. M. Maweikere; Olfie L. S. Benu (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this study is to calculate and analyze the profits of the home industry of Mr. Hamid's Robusta coffee, red bean powder. The data used in May 2021. The analysis of the data used in this study is an analysis of the profits of the home industry of "Hamid" red bean robusta coffee by calculating the difference between the revenue and the total cost used. Based on the results and discussions that have been carried out, it can be concluded that Mr. Hamid's business is profitable. The home industry business of red bean powder robusta coffee incurs a production cost of Rp. 2,435.012 with a profit rate obtained by the home industry of red bean powder robusta coffee in May 2021 of Rp. 2,464,988. To compare other businesses from previous studies, the calculation of revenue cost analysis where the R/C value of this business is 2.0, meaning that the home industry business of Mr. Hamid's red bean powder robusta coffee is higher, so this business is feasible to be maintained. Â